2016
DOI: 10.1038/srep29264
|View full text |Cite
|
Sign up to set email alerts
|

Transition of differential histone H3 methylation in photoreceptors and other retinal cells during retinal differentiation

Abstract: To analyze cell lineage-specific transitions in global transcriptional and epigenetic changes during retinogenesis, we purified retinal cells from normal mice during postnatal development into two fractions, namely, photoreceptors and other retinal cells, based on Cd73 expression, and performed RNA sequencing and ChIP sequencing of H3K27me3 and H3K4me3. Genes expressed in the photoreceptor lineage were marked with H3K4me3 in the Cd73-positive cell fraction; however, the level of H3K27me3 was very low in both C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…Retinalspecific ablation of Ezh2 leads to acceleration of photoreceptor terminal differentiation with premature expression of key photoreceptor genes in the postnatal retina (22,24). Dynamics of Ezh2 expression in the developing cochlear sensory epithelium also point to a regulatory role in terminal differentiation (34), but no similar data are available in the olfactory epithelium at present.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Retinalspecific ablation of Ezh2 leads to acceleration of photoreceptor terminal differentiation with premature expression of key photoreceptor genes in the postnatal retina (22,24). Dynamics of Ezh2 expression in the developing cochlear sensory epithelium also point to a regulatory role in terminal differentiation (34), but no similar data are available in the olfactory epithelium at present.…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, most of the early-onset retinal genes identified to be repressed at P5 in the KO (Fig. 6 A and B) are downstream targets of Ezh2 (22,24,25). Delayed up-regulation of Rho expression in the KO was also confirmed by immunostaining on P12 and P16 (Fig.…”
Section: Delayed Rod Outer Segment Biogenesis Followed By Early-onsetmentioning
confidence: 54%
See 1 more Smart Citation
“…This at the first glance seems highly unlikely, knowing the successive events necessary for cone commitment13, 27 and the epigenetic modifications occurring in rods and cones after their differentiation 45, 46. It was, nonetheless, recently shown that the downregulation of NRL in the adult retina provokes a cone-like phenotype with rod characteristic defects 47 .…”
Section: Discussionmentioning
confidence: 99%
“…In this work the authors described a unique epigenetic signature marking rod photoreceptor‐specific genes. The concept of a pattern of histone modifications specific of a particular cell type has also been explored by Ueno and collaborators . They discovered that photoreceptor‐specific loci were also marked by H3K4me3.…”
Section: Histone Modification Dynamics Reveal Global and Distinct Epimentioning
confidence: 99%